Marxismo y literatura / Raymond Williams ; prólogo de J.M. Castellet ; traducción de Pablo di Masso - Castellet, J. M. (1926-2014); Williams, Raymond (Historia, ciencia, sociedad ; 265)
Bibliogr.: p. 245-250.